Assembly and comparative analysis of the complete mitochondrial genome of the spice plant Cinnamomum longepaniculatum - Yanling Fan; Linxin Tan; Ruizhang Feng; Xin Zhao; Xiangdong Xu (BMC Plant Biology)
Abstract Background Cinnamomum longepaniculatum(Gamble) N. Chao ex H. W. Li (C. longepaniculatum), a species renowned for its leaves and twigs yielding essential oils, is extensively utilized as a vital raw material in traditional Chinese medicine, spice, and daily chemical products, and thus possesses both high economic value and significant scientific research value. However, to date, no detailed information on the mitochondrial genome (mitogenome) has been reported. Results The mitogenome of C. longepaniculatum was characterized by a linear structure, spanning 870,686 bp with 46.94% GC content. It encompassed 44 protein-coding genes (PCGs), 28 tRNAs, and 3 rRNAs. Numerous repetitive sequences were observed, including 317 simple sequence repeats (SSRs), 52 tandem repeats and 874 pairs of dispersed repeats. Phylogenetic analysis based on the 41 conserved mitochondrial PCGs of C. longepaniculatum reflected its close evolutionary affinity to C. camphora, followed by C. chekiangense and C. insularimontanum. Furthermore, dot-plot analysis revealed diverse homologous collinear regions between C. longepaniculatum and other species belonging to the Laurales. Specifically, the largest collinear blocks, spanning over 861 kb, accounted for 95.59% of the total proportion between C. longepaniculatum and Cinnamomum camphora, indicating a high degree of conservation and similarity in their mitogenome structures. Conclusions This study presents the initial assembly and annotation of C. longepaniculatum mitogenome, thereby enriching the limited repository of mitogenome sequences available for Laurales plants. These findings provide crucial molecular evidence for further studies on the evolutionary relationships and genomic evolution within the Laurales.